Changes in Timing and Precipitation of the East Asian Summer Monsoon over China Between 1960 and 2017 - Zeyu Dou; Binhui Liu; Mark Henderson; Wanying Zhou; Rong Ma; Mingyang Chen; Zhi Zhang (Earth)
The East Asian Summer Monsoon (EASM) is a critical component of the Earth’s climate system that brings substantial seasonal precipitation to China, contributing over 30 percent of summer half-year’s precipitation. Agriculture critically depends on the monsoon’s timing and precipitation, but the effects of climate change on its regional configuration remain poorly understood. We analyzed daily precipitation time series from 145 observation stations in eastern China to quantify the initial and final dates of the rainband steady phase and detect regional variations in monsoon duration and intensity from 1960 to 2017. Monsoon rainband precipitation declined until the mid-1980s, increased from the mid-1980s to 1998, and generally stabilized after that. During the weakening period, the rainband tended to reach mainland China earlier and to take longer to progress from south to north; those changes reversed during the strengthening period. When the EASM weakened, precipitation decreased in the north and south but not in the lower Yangtze and Huaihe river basins of East-Central China. When the EASM strengthened, precipitation increased in all regions, with changes in extreme precipitation generally greater than the changes in overall precipitation. Overall, the moisture imbalance between regions has intensified, reinforcing the pattern of “southern floods, northern droughts” in China.